Prediction of Fatigue Time Life from Adapted Juvinall's Method for Forklift Simulator Parts Obtained by 3D Printing - Miwa, Vinícius Hiroshi Souza; Dos Santos, Laiane Silva; Acypreste, Yago Levi; Calassa, Felipe; Tamayo, Daimer Velázquez; Ditrich, Lucas; de Oliveira Acevedo, Ruben Bentes; Martins, Marcelo Sampaio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Additive manufacturing, particularly 3D printing, has proven to be an efficient solution for low-scale production applications. In this study, components for 65 units of forklift simulators were fabricated using 3D printing technologies, such as Selective Laser Sintering (SLS) and Stereolithography (SLA). The objective of this work is to estimate the service life of these simulator components and determine the required quantity of replacement parts. To achieve this, a fatigue life analysis was implemented using the Juvinall method, adapted for the materials employed in the printing processes. The calculated fatigue life and part quantities were subsequently validated through Finite Element Method (FEM) simulations. The results showed a strong correlation between both approaches, indicating that all components can withstand the programmed operational design life of five years.